An automated method for tendon image segmentation on ultrasound using grey-level co-occurrence matrix features and hidden Gaussian Markov random fields - Scott, I; Connell, D; Moulton, D; Waters, S; Namburete, A; Arnab, A; Malliaras, P (Elsevier, 2023)
Background: Despite knowledge of qualitative changes that occur on ultrasound in tendinopathy, there is currently no objective and reliable means to quantify the severity or prognosis of tendinopathy on ultrasound.